Novel Human FCGR1A Variants Affect CD64 Functions and Are Risk Factors for Sarcoidosis - Wu, Jianming; Li, Yunfang; Rendahl, Aaron; Bhargava, Maneesh (Frontiers in Immunology, 2022)
CD64 (or FcγRIA) is the sole functional high affinity IgG Fc receptor coded by FCGR1A gene in humans. The FCGR1A genetics has not been comprehensively investigated and effects of human FCGR1A variants on immune functions remain unknown. In the current study, we identified three novel FCGR1A variants including the single nucleotide variant (SNV) rs1848781 (c.-131) in the proximal FCGR1A gene promoter region, the rs587598788 indel variant within the FCGR1A intron 5, and the non-synonymous SNV rs1050204 (c.970G>A or FcRIA p.D324N) in the FCGR1A coding region. Genotype-phenotype analyses revealed that SNV rs1848781 genotypes were significantly associated with CD64 expression levels. Promoter reporter assays show that rs1848781G allele had significantly higher promoter activity than the rs1848781C, confirming that the rs1848781 is a functional FCGR1A SNV affecting promoter activity and gene expression. The rs587598788 indel genotypes were also significantly associated with levels of CD64 expression. Moreover, the non-synonymous SNV rs1050204 (FcRIA-p.D324N) alleles significantly affected CD64-mediated phagocytosis, degranulation, and pro-inflammatory cytokine productions. Genetic analyses revealed that FCGR1A genotypes were significantly associated with sarcoidosis susceptibility and severity. Our data suggest that FCGR1A genetic variants may affect immune responses and play a role in sarcoidosis.